The Coal Transition : Mitigating Social and Labor Impacts - Cunningham, Wendy (World Bank, Washington, DC, 2021)
Realizing the objectives of the Paris Agreement on climate change will necessitate a timely transition of the global energy system out of coal, but evidence from Europe, China, and the United States shows that the coal transition can lead to massive job losses. This paper develops a comprehensive policy approach to assist affected workers and communities. Based on a conceptual framework that distinguishes between pre-layoff planning, pre-layoff assistance and post-layoff assistance, it discusses the main instruments for mitigating social and labor impacts, in particular income support and active labor market policies. In addition, it considers the institutional context, the dynamics of change, and implementation issues. The paper argues that while challenges resulting from the coal transition should not be minimized, the sound management of job displacements can contribute to mitigating the social consequences, strengthen morale and productivity, and improve the efficiency of structural change.